‘Boleiros - era uma vez o futebol ’:a figurational analysis - de Souza, Daniel Minuzzi; Boschilia, Bruno; Quaranta, André Marsiglia; de Oliveira, Alessandra Weiss Ferraz; Júnior, Wanderley Marchi (Revista da ALESDE, 2024)
The sports phenomenon has been shaped as a complex manifestation in society and football is an object researched in distinct areas of knowledge being Physical Education (PE) a privileged field for studies development. To study such phenomenon, we sought the relevance of the social approach. For such, the Competitive Games Analysis Models proposed by Norbert Elias’s Configurational Sociology was selected. The media product analyzed was the film ‘Boleiros - era uma vez o futebol’. Methodologically, we tried to develop a media study adapted as a media product analysis. The discussion process focused on the 6 stories presented in the film, seeking to identify the chains of functional interdependencies and the degrees of reciprocal multipolar dependence on social relations. We consider this strategy a didactic-pedagogical resource in formal and informal training processes, as well as a method to consolidate possibilities for understanding the football phenomenon through Sociology of Sport.